REVIEW OF THE TRAGIC ODES OF JERRY GARCIA AND THE GRATEFUL DEAD: MYSTERY DANCES IN THE MAGIC THEATER, BY BRENT WOOD - Coffman, Christopher K. (Dialogue, 9(1,2), 2022)
Brent Wood’s The Tragic Odes of Jerry Garcia and the Grateful Dead: Mystery Dances in the Magic Theater is the latest volume in the Ashgate Popular and Folk Music Series. Like other texts in the series, it undertakes musicological analysis of its subject in the context of interpretations that draw on a wide variety of socio-cultural considerations and scholarly fields. For those who teach with the Grateful Dead, Wood’s text offers much on a number of fronts: its interdisciplinary scope provides fresh insights about the Grateful Dead in relation to topics in literary studies, classics, philosophy, musicology, and history, among other disciplines...
Keywords: Type of access: Open Access